Ghrelin-Mediated Regeneration and Plasticity After Nervous System Injury - Stoyanova, Irina; Lutz, David (Frontiers in Cell and Developmental Biology, 2021)
The nervous system is highly vulnerable to different factors which may cause injury followed by an acute or chronic neurodegeneration. Injury involves a loss of extracellular matrix integrity, neuronal circuitry disintegration, and impairment of synaptic activity and plasticity. Application of pleiotropic molecules initiating extracellular matrix reorganization and stimulating neuronal plasticity could prevent propagation of the degeneration into the tissue surrounding the injury. To find an omnipotent therapeutic molecule, however, seems to be a fairly ambitious task, given the complex demands of the regenerating nervous system that need to be fulfilled. Among the vast number of candidates examined so far, the neuropeptide and hormone ghrelin holds within a very promising therapeutic potential with its ability to cross the blood-brain barrier, to balance metabolic processes, and to stimulate neuro repair and neuroactivity. Compared with its well-established systemic effects in treatment of metabolism-related disorders, the therapeutic potential of ghrelin on neuroregeneration upon injury has received lesser appreciation though. Here we discuss emerging concepts of ghrelin as an omnipotent player unleashing developmentally related molecular cues and morphogenic cascades, which could attenuate and/or counteract acute and chronic neurodegeneration.